THE ROLE OF MADRASAH IN BUILDING STUDENTS' LEARNING INDEPENDENCE THROUGH QUR'ANI SPIRITUAL VALUES IN LEARNING ACTIVITIES AT MTS NURUL QUR'AN - Rofi, Moh. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Madrasah Tsanawiyah Nurul Qur'an is an educational institution that combines general education and Qur'anic spiritual values in daily learning activities. This research tries to explore the role of MTs Nurul Qur'an in building student learning independence through the implementation of Qur'anic spiritual values in the teaching and learning process. The research methodology used is a qualitative approach using observation methods, in-depth interviews and document analysis. Observations were carried out to observe the implementation of spiritual values in learning activities, while in-depth interviews were conducted with teachers, students and parents to obtain a comprehensive perspective regarding the role of madrasas in supporting students' learning independence. Document analysis was carried out on the curriculum, learning modules and student evaluation results. The research results show that MTs Nurul Qur'an has succeeded in building student learning independence through several strategies. First, by integrating Qur'anic values such as honesty, discipline, responsibility and sincerity in every subject through emphasizing the importance of good intentions in studying and applying the learning etiquette taught by the Prophet Muhammad. Second, there is a tahfidzul Qur'an program which is routinely carried out every morning before starting formal lessons. This program not only improves students' ability to memorize the Al-Qur'an, but also trains discipline and perseverance in studying. Apart from that, madrasas also provide extracurricular activities that strengthen spiritual values and independent learning, such as express Islamic boarding school activities, yellow book studies, and leadership training. These activities help students to apply the values they learn in everyday life and improve their skills in working independently and in groups. This research concludes that the integration of Qur'anic spiritual values in learning activities at MTs Nurul Qur'an has a significant positive impact on student learning independence. By building strong character and noble morals, students not only become more independent in learning but also have strong intrinsic motivation to continue developing themselves. These findings provide valuable insights for other educational institutions that wish to implement a similar approach in an effort to build independence and superior student character.